On anti‐abortion violence. (19th January 2021) - Williams, Jeremy
Abstract: Anti‐abortion violence ('AAV') is anathema to almost everyone, on all sides of the abortion debate. Yet, as this article aims to show, it is far more difficult than has previously been recognised to avoid the deeply unpalatable conclusion that it can sometimes be justified. Some of the most frequently‐occupied positions on the morality of abortion will imply precisely that conclusion, I argue, unless conjoined with an especially stringent and unattractive form of pacifism. This is true not only of strict anti‐abortion views, but also, more surprisingly, of some of the most familiar and influential moderate defences of abortion rights. The latter conclusion raises the question, which further work will be required to fully resolve, of what our account of abortion ethics and prenatal moral status must be if it is to enable reconciliation of the common‐sense rejections of both pacifism and AAV. I end with reasons to expect that the path to an account that satisfies this demand, without generating further significant intuitive problems, will be far from straightforward.